Evaluation of the effects of variation in ingredient composition on the eating qualities of suya. (2004)
The semimembrenous muscle from singed beef carcass was trimmed of all visible bones andn connective tissue. The meat was sliced into thin sheet of 0.15- 0.3cm thick and between 5.0 - 9.0 cm long. The experiment comprised of five treatments. Treatment one (T1) In served as the control, with all ingredients present while ginger, red pepper, curry and white pepper were absent in T2, T3, T4 and T5 respectively. A total of 30 sticks of suya with an average weight of 34.92 + 5.03gram of meat per stick were prepared for each treatment. The stick meat was properly coated with each respective ingredient mixture. The coated stick meat was roasted on a glowing, smokeless fire for 30 minutes with regular turning of the product. The result of the study showed that the least product yield was recorded where the percent loss was highest (P<0.05) in treatment four (T4). The taste panel score revealed that apart from hotness (pungency) which was dependent (P<0.05) on the presence of red pepper (Capsicum fructescens) all other eating qualities such as flavor, tenderness, juiciness and overall acceptability were not affected (P>0.05) by the absence of any of the four spices under investigation.